THE ROLE OF FINANCIAL SERVICES IN GHANA’S OIL AND GAS INDUSTRY: THE CASE OF OPERATOR EXTRA EXPENSE INSURANCE - Anastas Kabral Nyamikeh (European Scientific Journal, ESJ, 2014)
The strike of crude oil in Ghana has a concomitant spark of the role of other sectors in the economy towards the realization of the benefits that ought to spawn from this naturally endowed resource. The financial services sector, in this connection, insurance, is automatically stimulated to play no mean role in providing insurance services to cover the risks associated not only with the mainstream germane activities of extracting the oil and gas but also other ancillary services that support the exploration, development and production of black gold This paper discusses the role of operator extra expense insurance in the oil and gas economy, which inter alia covers the extra expenses oil companies may have to incur to control wells out of control or experiencing blowouts or kicks